ANALYSIS OF GENDER STREAMING IMPLEMENTATION IN PLACEMENT OF FEMALE POLICE OFFICERS AS COMPETENCE-BASED SECTOR POLICE CHIEF AT POLDA METRO JAYA - Sariwaty Siregar, Yuliani; Nurdin, Nurliah; Hadi Rivai, Firman (INDONESIAN JOURNAL OF SOCIAL POLITIC AND POLICY STUDIES, 2024)
This study aims to analyze the gender mainstreaming of the Police at Polda Metro Jaya through the placement of female police officers as regional leaders (Kapolsek) with the socio-cultural Indonesian nation, which still holds the principle that a woman's job is to take care of the household so that it does not give women freedom to have a career, as well as the police profession. Women are seen by the public as only part of the image of the police, where the presence of female police officers is complementary to carrying out police duties and is only placed in staff, personal secretary and administration functions. This study used a descriptive qualitative method by conducting interviews and field observations. The results of the study have been that there is a policy in the context of gender mainstreaming with the placement of female police officers as leaders in the sector police (Kapolsek) and there is no difference in the placement of female police officers and male police officers as police chiefs but the successful implementation of gender mainstreaming has not been optimally implemented due to the lack of motivation from Female police due to the challenges of police duties at Polda Metro Jaya which are quite complex and the work of the police which is quite heavy, dominantly related to criminal cases and influenced by population density and area as well as religious/community leaders in the sector police (Polsek) so that the Kapolsek is required to be ready to carry out their duties 24 hours to maintain security and order in the community.